2014
DOI: 10.1080/10926771.2014.883458
|View full text |Cite
|
Sign up to set email alerts
|

Social-Cognitive Moderators of the Relationship between Peer Victimization and Suicidal Ideation among Psychiatrically Hospitalized Adolescents

Abstract: Peer victimization among children and adolescents is a major public health concern, given its widespread individual and societal ramifications. Victims of peer aggression often face significant levels of psychological distress and social difficulties, such as depression, suicidal ideation, suicide attempts, and social rejection. The purpose of the present study was to examine whether cognitive distortions and perceptions of social support moderate the association between peer victimization and suicidal thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…The obtained results were consistent to the findings of previous studies conducted by Fazakas-DeHoog et al (2017), Jager-Hyman et al 2014, and Wolff et al (2014), who proposed that cognitive distortion was significantly and positively related to suicidal ideation. This represented that individuals with cognitive distortions would be more likely to develop suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The obtained results were consistent to the findings of previous studies conducted by Fazakas-DeHoog et al (2017), Jager-Hyman et al 2014, and Wolff et al (2014), who proposed that cognitive distortion was significantly and positively related to suicidal ideation. This represented that individuals with cognitive distortions would be more likely to develop suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
“…Theoretically, cognitive distortion is the initial factor causing development of suicidal ideation. This was supported by the studies conducted by Fazakas-DeHoog et al 2017, Jager-Hyman et al 2014, and Wolff et al (2014), who proposed that cognitive distortion was significantly related to suicidal ideation. However, these findings were contradicted to the result of Khan et al (2014) who found that there was no significant relationship between cognitive distortion and suicidal ideation.…”
Section: Literature Reviewmentioning
confidence: 67%
See 2 more Smart Citations
“…A total of four studies focused on factors related to an individual’s cognitive style. Less negative interpretations of oneself, the world, and the future buffered the link between depressive symptoms and suicidal ideation (Chang, Lin, & Lin, 2007), while lower levels of negative self-talk and cognitive errors moderated the relationship between peer victimization and suicidal ideation (Wolff et al, 2014), However, although the latter study found a buffering effect at both low and high levels of peer victimization, the buffering effect was greater at low levels of peer victimization. In contrast, Miller and Esposito-Smythers (2013) showed that neither cognitive errors nor the negative cognitive triad moderated the link between a history of child abuse and suicidal ideation.…”
Section: Resultsmentioning
confidence: 77%